Histopathologic Outcomes of Robotic Radical Prostatectomy - Vipul R. Patel; Sagar Shah; David Arend (The Scientific World Journal)
Robotically assisted laparoscopic radical prostatectomy is a minimally invasive alternative for the treatment of prostate cancer. We report the histopathologic and shortterm PSA outcomes of 500 robotic radical prostatectomies. Five hundred patients underwent robotic radical prostatectomy. The procedure was performed via a six trocar transperitoneal technique. Prostatectomy specimens were analyzed for TNM stage, Gleason’s grade, tumor location, volume, specimen weight, seminal vesicle involvement, and margin status. A positive margin was reported if cancer cells were found at the inked specimen margin. PSA data were collected every 3 months for the first year, then every 6 months for a year, then yearly. The average preoperative PSA was 6.9 (1–90) with Gleason’s score of 5 (2%), 6 (52%), 7 (40%), 8 (4%), and 9 (2%); postoperatively, histopathologic analysis showed Gleason's 6 (44%), 7 (42%), 8 (10%), and 9 (4%); 10, 5, 63, 15, 5, and 2% had pathologic stage T2a, T2b, T2c, T3a, T3b, and T4, respectively. Positive margin rate was 9.4% for the entire series. The positive margin rate per 100 cases was: 13% (1–100), 8% (101–200), 13% (201–300), 5% (301–400), and 8% (401–500). By stage, it was 2, 4, and 2.5% for T2a, T2b, T2c tumors; 23% (T3a), 46% (T3b), and 53% (T4a). For organ-confined disease (T2), the margin rate was 2.5% and it was 31% for nonorgan-confined disease. There were a total of 47 positive margins, 26 (56%) posterolateral, 4 (8.5%) apical, 4 (8.5%) bladder neck, 2 (4%) seminal vesicle, and 11 (23%) multifocal. Ninety-five percent of patients (n = 500) have undetectable PSA (<0.1) at average follow-up of 9.7 months. Recurrence has only been seen with nonorgan-confined tumors. Of those patients with a minimum follow-up of 1 year (average 15.7 months), 95% have undetectable PSA (<0.1). Our initial experience with robotic radical prostatectomy is promising. Histopathologic outcomes are acceptable with a low overall, positive margin rate. Shortterm biochemical recurrence-free survival has also been good. We believe that the precise dissection allowed by the advantages of laparoscopic robotic surgery will translate into excellent long-term oncologic outcomes. At this time, the lack of maturity of the PSA data prevent definitive comparison to the open approach.